Ultrasonic Investigation on Hydroxy Ethyl Propyl Cellulose (HEPC) Solution at Different Concentration and pH - Aruna, S.; Thiyagarajan, R.; Panneerselvam, A. (Asian Journal of Chemistry, 2020)
The ultrasonic investigation is one of the most effective and economical technique to analyze the nature of the matter. Ultrasonic techniques provide valuable information about the physico-chemical nature of the aqueous solutions. Thus, the propagation characteristics of an acoustical wave in solutions are used to study the nature of intermolecular interaction. In this work, the ultrasonic velocity, viscosity and density studies were determined to study the effect of concentration and pH in the aqueous hydroxyethyl propyl cellulose (HEPC) solutions at different temperatures (303, 313 and 323 K). From the observed values, the necessary related ultrasonic parameters are calculated and their variations are discussed. The findings from the result say the variations in the velocity and absorption coefficient values are only due to the conformational changes that occur in the HEPC solution.